Synthetic Study on the Relationship Between Structure and Sweet Taste Properties of Steviol Glycosides - Grant Dubois; Mani Upreti; Indra Prakash (Molecules, 2012)
The structure activity relationship between the C16-C17 methylene double bond on the aglycone of steviol glycosides and the corresponding impact on their sweet taste has been reported here for the first time. It has been observed that converting stevioside and rebaudioside A to their corresponding ketones by switching the doubly bonded methylene on C-17 for a ketone group actually removes the sweet taste properties of these molecules completely. Regenerating the original molecules tends to restore the sweet taste of both the steviol glycosides. Thus this C16-C17 methylene double bond in rebaudioside A and stevioside can be regarded as a pharmacophore essential for the sweetness property of these molecules.